The Effect of Training, Competence, and Career Development on Employee Performance at NataKisah PT. Dua Bintang Muda Cemerlang - Ramadhani, Nabiilah Shinta; Samsudin, Acep (Journal of Business Management and Economic Development, 2025)
The aim of this research is to ascertain and analyze training, competence, and career development have an effect on employee performance. The objects used in this study were 35 employees of NataKisah PT. Dua Bintang Muda Cemerlang. This study used primary data supported by data collection techniques through questionnaires. The author uses a quantitative research method with a technique from the sample using a Likert scale. To analyze the study using validity tests, reliability tests, classical assumption tests, F tests, t tests, and from the analysis of the tests used, the processing used SPSS 24. This study produced data showing that the results of the t test of training and competence partially had a significant effect on employee performance, while career development had a significant negative effect on employee performance. For the results of the F test, the F count result was 71.414, which was greater than Ftable, which was 2.90 with a significance value of 0.000 <0.05. This means that training, competence, and career development have a simultaneous effect on employee performance.